IMAGE RECONSTRUCTION USING ELECTRICAL TOMOGRAPHY FOR OBJECT WITH VARIATION IN TEMPERATURE - WIJAYA (NIM : 13311020); JOSEPH RAMOS PDH (NIM : 13311042);, WILLIAM
Temperature is a physical parameter that is ignored in the process of reconstruction of the cross section of the object. In the industry, the temperature is an important parameter that can adjust the quality of the resulting product. Electrical tomography can be used as a solution to reconstruct the object by utilizing a cross-sectional resistivity changes due to the temperature difference. In this research, the object used is water with aluminum cylinder placed in PVC containers. Testing is done using real objects and simulation object that using parameters based on actual conditions. The process of data acquisition on both the object using neighboring method. The increase in temperature of the object selected by 10Ã‚Â°C to obtain a large enough change in resistivity. The process of image reconstruction using regularization parameter is worth 2 and 6 times the number of iterations to get the results that match the object used. The difference between simulation results and experimental reconstruction clearly visible on the rise in temperature. Water on the simulation object has a resistivity coefficient of 22.83 Ωm and temperature coefficient of 0.0191/Ã‚Â°C so that an increase in resistivity when the temperature changes.